Implementation of AudioVisual Media in Enhancing Catholic Religious Education Learning Motivation among Elementary School Students - Halarry Mega Pulo; Yosep Belen Keban; Petrus Tukan (International Journal of Christian Education and Philosophical Inquiry, 2025)
This study aims to analyze the implementation of audio-visual media in Catholic Religious Education learning to enhance learning motivation among third-grade students at Inpres Jongwolor Elementary School. The research employed a qualitative approach with descriptive design. Research subjects consisted of one Catholic Religious Education teacher and five third-grade students selected purposively. Data were collected through unstructured interviews, participatory observation, and documentation, then analyzed using the Miles and Huberman interactive model. The results indicate that audio-visual media usage in Catholic Religious Education learning remains suboptimal due to limited internet access, high data costs, and insufficient teacher technology competence. However, when implemented, audio-visual media significantly increases learning motivation, reflected in enhanced enthusiasm, interest, attention, and active student participation during learning activities. Audio-visual media proved effective in visualizing abstract concepts of spiritual and moral values, making them more concrete and comprehensible. This research provides empirical evidence that optimizing audio-visual media usage can serve as an effective strategy to improve Catholic Religious Education learning quality at the elementary school level.